A review of theories, pedagogies and vocabulary learning tasks of English vocabulary learning apps for Chinese EFL learners - Li Congxin (Journal of China Computer-Assisted Language Learning)
Among a growing body of mobile-assisted-language-learning (MALL) studies, vocabulary application (app) studies have comprised an unprecedented proportion. However, there has been insufficient discussion about the fundamental language learning theories and pedagogies underlying app design. This study aims to fill this gap by conceptualising and theorising the design of English vocabulary learning apps with a focused analysis of their task features with relation to vocabulary learning strategies (VLS), language learning theories and pedagogies. Four Chinese–English vocabulary learning apps were purposively sampled. The results show that the design of the four evaluated apps incorporates principles from four distinct language learning theories: behaviourism, input-based emergentism, sociocultural theory and information and cognitive processing theories. The four apps’ tasks and user interfaces were analysed to generate codes for task classification. These task-related codes were further classified under the categories of Schmitt’s VLS taxonomy and under pedagogical categories based on the definitions of pedagogies and VLS codes and the intended classroom practice. Vocabulary pedagogies were further linked with theories to shed light on the theoretical foundations for the apps’ use of learning tasks and VLS as well as on the pedagogical prospects of vocabulary learning apps.